Social media identity in niche sports: the use of social media by U.S. rugby - Kucharski, Joseph (Kansas State University, 2017)
Rugby was created in 1876 and since then has expanded from the colleges of England to a globally played sport. Rugby, along with many other sports such as lacrosse and cricket, has found difficulties in obtaining mainstream media attention in the United States. This series of in-depth interviews explore how U.S. rugby may be able to utilize social media to elevate rugby to mainstream media status. This study will use in-depth interviews to understand the strategies of Division 1 Men’s U.S. Rugby social media officials and media strategists from the Professional Rugby Organization (PRO). These in-depth interviews will first identify what strategies rugby has used, then will evaluate which strategies efficiency. Second, the in-depth interviews of the club-level social media chairs will also be asked about his or her background in social media strategy. The information collected will be used to make recommendations as to what professional rugby and club-level rugby strategies should be used on social media. The information will also be used to identify what level social media rugby chairs should be educated or trained in using social media, if any. This study also explored the outcomes of the social media efforts for the advancement of rugby in the U.S. as well as emerging sports in the future.
Keywords: Social media; Mass communicationRugby